Governing bodies that consider joining or creating federations. (January 2015) - Howarth, Eleanor
This article reports the findings of a research study exploring what motivates governing bodies to consider joining or creating a federation, their experiences of the process and the barriers faced. The research methodology involved semi-structured telephone interviews, face-to-face interviews and analysis of relevant documentation. The varied circumstances of participating schools revealed a wide range of drivers for considering federation, which were commonly underpinned by school improvement, professional leadership and pooling resources. Although governors' experiences of the process of becoming a federation were largely positive, the study identified a number of common barriers. The study concludes that, despite the benefits of federation, unlike multi-academy trusts its relatively low profile in current education policy has created a barrier for governing bodies. It is recommended that the government provides the same level of guidance and support for schools considering federation as they do for those considering academization.